Gene cloning, expression pattern analysis, and subcellular localization of LIKE HETEROCHROMATIN PROTEIN 1 (LHP1) homologs in chrysanthemum (Chrysanthemum morifolium Ramat.) - Wu, Zhiping; Gao, Yike; Fan, Min; Gao, Yaohui (Cellular and Molecular Biology, 2019)
Flowering is a very important developmental stage in the plant life cycle. LIKE HETEROCHROMATIN PROTEIN 1 (LHP1) has been shown to participate in epigenetic silencing of flowering genes. Here, for the first time, we isolated and characterized six CmLHP1 homolog genes from the important day-neutral ornamental Chrysanthemum morifolium cultivar ‘Jin budiao’. These homolog genes were most likely generated by whole-genome duplication. Bioinformatic analysis showed that chrysanthemum LHP1 homologs present low similarity to other plant LHP1-like genes. However, three nuclear localization signals and two domains were highly conserved among them. The secondary structures of the CmLHP1 homologs mainly include Î±-helices and random coils, indicating that the proteins are mixed proteins. Phylogenetic tree analysis indicated that the six CmLHP1 genes constituted a small clade and had the closest relationship with LsLHP1 (Lactuca sativa LHP1). Quantitative RT-PCR analysis showed that the CmLHP1 homologs were expressed in different tissues during the developmental period of chrysanthemum, but they were highly expressed in the buds, especially during the key S1 stage of the inflorescence. Furthermore, the expression patterns of CmLHP1 homologs showed divergence under different photoperiods. Both CmLHP1b and CmLHP1e exhibited photoperiod sensitivity in leaves. Intriguingly, CmLHP1c was insensitive to photoperiod in both the shoot apexes and the leaves. Subcellular localization revealed that the six CmLHP1 proteins were located in the nucleus. These results reveal that CmLHP1 homolog genes could be strong candidates as important regulators of flowering time in chrysanthemum.